Coughs and sneezes spread diseases-poster 1942 (London, 1942)
1942 1939-1945 "Coughs and sneezes spread diseases-poster 1942" [HFR0014], 1942 Ministry of Health / Central Council for Health Education poster in a series designed by cartoonist Herbert Mayo Bateman. The campaign was launched in October 1942 to promote fitness at work and to combat absenteeism. This cartoon shows women working with shell casings in a munitions factory.